Sudden death due to gas gangrene caused by Clostridium septicum in goats - Gazioglu, Abdullah; Karagulle, Burcu; Yuksel, Hayati; Acik, M. Nuri; Kececi, Hakan; Dortbudak, Muhammet Bahaeddin; Cetinkaya, Burhan (Bmc, 2018)
BackgroundEven though gas gangrene caused by Clostridium septicum in goats is mentioned in the classical textbooks, we have not managed to find any case description in the literature.Case presentationClinical signs resembling gas gangrene such as subcutaneous bloating, edema and crepitation were detected at various body parts of nine pregnant animals at the ages of 2-3years on a hair goat farm (n=170) located in Bingol province, Eastern Turkey. Five of these suspected animals with severe clinical symptoms died within 2 days. Various samples such as internal organs, edematous skin and edema fluid collected from dead and live animals were analyzed for the presence of clostridial agents by histopathological and microbiological methods. As a result of macroscopic and microscopic examination, lesions of gas gangrene were detected. The suspected isolates were identified and confirmed as C. septicum by bacteriological and molecular methods.ConclusionThe present study was the first to report identification of C. septicum as primary agent in the gas gangrene of goats.
Keywords: Clostridium septicum; Goat; Gas gangrene